2000
DOI: 10.1097/00004647-200012000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged but Delayed Postischemic Hypothermia: A Long-term Outcome Study in the Rat Middle Cerebral Artery Occlusion Model

Abstract: Delayed but prolonged hypothermia persistently decreases cell death and functional deficits after global cerebral ischemia in rodents. Postischemic hypothermia also reduces infarction after middle cerebral artery occlusion (MCAO) in rat. Because initial neuroprotection is sometimes transient and may not subserve functional recovery, especially on demanding tasks, the authors examined whether postischemic cooling would persistently reduce infarction and forelimb reaching deficits after MCAO. Male spontaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
115
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 208 publications
(121 citation statements)
references
References 33 publications
3
115
0
3
Order By: Relevance
“…82 This chronic loss could be prevented by extending the duration of moderate (32 to 34°C ) hypothermia to 48 hours or more, even when the start of cooling was delayed until 6 hours after reperfusion. 83,84 How much should we cool?…”
Section: The 'Pharmacodynamics' Of Hypothermiamentioning
confidence: 99%
“…82 This chronic loss could be prevented by extending the duration of moderate (32 to 34°C ) hypothermia to 48 hours or more, even when the start of cooling was delayed until 6 hours after reperfusion. 83,84 How much should we cool?…”
Section: The 'Pharmacodynamics' Of Hypothermiamentioning
confidence: 99%
“…Mild (33-36°C) or moderate (28-32°C) hypothermia is one of the strongest neuroprotectants identified to date that protect against cerebral ischemia [1,3,14], but the exact mechanisms for its protective effects are not fully understood [15]. We have previously reported that intraischemic moderate hypothermia (30 °C) reduces infarct size in focal ischemia by regulating the Akt survival pathways [14].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies established that cooling during global or focal cerebral ischemia greatly diminishes cell death and promotes functional recovery (for comprehensive reviews, see Ginsberg et al, 1992;Maher and Hachinski, 1993;Thornhill and Corbett, 2001;Wagner and Zuccarello, 2005). Although initially controversial (Dietrich et al, 1993), delayed postischemic hypothermia also reduces cell death and improves functional recovery (Carroll and Beek, 1992;Colbourne and Corbett, 1995;Colbourne et al, 2000;Maier et al, 1998;Yanamoto et al, 1996); therefore, hypothermia has great potential as a clinical therapy. Indeed, recent studies show that systemic hypothermia improves survival and recovery in outof-hospital cardiac arrest victims (Bernard et al, 2002; The Hypothermia After Cardiac Arrest Study Group, 2002).…”
Section: Introductionmentioning
confidence: 99%